Pengaruh Model Problem Based Learning terhadap Peningkatan Kemampuan Literasi Sains Siswa Sekolah Dasar - Azka, Nabila Wardatul; Putri, Hafiziani Eka; Rahayu, Puji (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
The low scientific literacy ability of elementary school students is the basis of this research. This study aims to find out and analyze: 1) increasing the scientific literacy abilities of students who use the PBL model with students who use conventional learning; 2) the effect of applying the model PBL on students' scientific literacy abilities. The type of research used is quasi-experimental research with design non-equivalent control group and techniques purposive sampling. The sample for this study was fourth grade students at one of the public elementary schools in Purwakarta, totaling 50 students with 25 students in grade IV A and 25 students in grade IV B. Based on the results of the research, the conclusions were obtained: 1) The scientific literacy skills of students using the PBL model were increased. better compared to students who use conventional learning; 2) there is an influence from the application of the model PBL on students' scientific literacy abilities.